Small but powerful—local value chains and sustainability-oriented approaches in the agri-food sector - Susanne Royer; Maike Simon (Business and Society Review, 2023)
Regional and local value creation is seen as one solution for reducing the environmental impact of the agri-food system. The point of reference for this research is the powerless position of small actors in agri-food chains. This paper gives insights into the motivation of small-scale producers in developed countries to exit national and export markets and to opt for a sustainability orientation. Specifically, we explore how the powerlessness of small actors in global value chains may fuel the formation of regional and local value chains. Through a regional case study, we map the dairy value system and identify three different value chain structures in the Northern German dairy industry. Then, we illustrate how some small (organic) raw milk producers have changed their position in the value chain and bargaining strength by following different upgrading strategies. Their increase in bargaining power comes with efficiency losses and increased risk. Implications for small-scale producers and society are discussed and brought together in a framework that demonstrates the drivers and challenges for sustainability-oriented small-scale agricultural producers to achieve a stable and competitive position within the market.
Keywords: 330; dairy industry; sustainability; upgrading strategies; value chain